2021
DOI: 10.3390/biom11111734
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Chronic Central Leptin Infusion on Activation of Insulin Signaling Pathways in Adipose Tissue and Liver Are Related to Changes in the Inflammatory Environment

Abstract: Leptin modulates insulin signaling and this involves the Akt pathway, which is influenced by changes in the inflammatory environment and with leptin regulating cytokine synthesis. We evaluated the association between activation of the insulin-signaling pathway and alterations in pro- and anti-inflammatory cytokine levels in inguinal fat and liver of chronic central leptin infused (L), pair-fed (PF), and control rats. Signal transducer and activator of transcription 3 (STAT3) phosphorylation was increased in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Although we utilized a new, single set of animals, we have tested several parameters using old and current samples in the same three experimental groups with similar results. In addition, as we reported in previous studies performed using this experimental model with other tissues [ 14 , 65 , 66 ], we used five animals per group, estimating a 95% confidence level and reasonable and significant differences in the studied variables. In spite of the treatment performed, our results, for all studied parameters, showed low variability within each experimental group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we utilized a new, single set of animals, we have tested several parameters using old and current samples in the same three experimental groups with similar results. In addition, as we reported in previous studies performed using this experimental model with other tissues [ 14 , 65 , 66 ], we used five animals per group, estimating a 95% confidence level and reasonable and significant differences in the studied variables. In spite of the treatment performed, our results, for all studied parameters, showed low variability within each experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…Crosstalk between leptin and insulin signaling regulates not only intermediate metabolism, but also shared signaling targets. In this way, the effects of leptin on glucose metabolism, as well as on insulin signaling, are divergent in several organs and adipose tissue depots, increasing glucose metabolism and insulin signaling in the skeletal muscle and liver and reducing it in several fat depots [ 6 , 14 ]. Insulin signaling modulates fatty acid synthesis, increasing the generation of reduced nicotinamide adenine dinucleotide phosphate (NADPH) for lipid synthesis [ 15 ] and the expression of key enzymes for fatty acid synthesis through PI3K/Akt signaling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 is a nuclear transcription factor that is phosphorylated and activated by JAK2 (tyrosine-protein kinase JAK2) to form an activated homologous dimer that enters the nucleus to activate CPT1A transcription. Furthermore, STAT3 is required for leptin signaling transduction and activation ( 46 ). Our immunoblotting results showed that risperidone decreased STAT3 and CPT1A expression as well as their phosphorylation levels in differentiated and undifferentiated 3T3-L1 cells, which was not an indirect result of risperidone-induced cell differentiation ( Figures 7A,H ).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen rats were anesthetized, positioned in a stereotaxic apparatus and treated as previously reported [ 21 , 22 ] after a fasting period of 12 h. Concisely, a cannula, coupled to an osmotic minipump (Alzet, Durect Corp., Cupertino, CA, USA) which contained either vehicle (saline 0.9% plus 1% serum albumin) or leptin, was implanted into the right cerebral ventricle. The leptin was previously dissolved in saline plus 1% bovine serum albumin (BSA), and the rats were treated icv for 14 days with either vehicle or leptin (12 μg/day).…”
Section: Methodsmentioning
confidence: 99%